Digital Disruption and the Future of Leadership: An Interview With Rick Haythornthwaite, Chairman of Centrica and MasterCard. (October 2016) - Bolden, Richard; O'Regan, Nicholas
Unprecedented changes in the nature and prevalence of digital technology have significant implications for leadership theory, practice, and development that, as yet, remain largely unexplored in mainstream academic literature. This article features an interview with Rick Haythornthwaite, Chairman of global businesses including Centrica and MasterCard, where he reflects on the ways in which digital disruption is impacting upon the nature of leadership and strategic practice. It is accompanied by a commentary that highlights the importance of factors such as context, trust, ethics, and purpose in a fast moving corporate world.